APPLICATION OF RENEWABLE ENERGY SOURCES IN TERMS OF ECONOMIC, ENVIRONMENTAL AND SOCIAL SUSTAINABILITY - Mirjana Jokanović; Dušan Golubović; Blagoje Šupić; Aleksandra Koprivica (Applied Engineering Letters, 2018)
We are witnesses of everyday changes, which can bring the world into the question of survival. On the other hand, the progress and the speed of changes are the keys of success. What is important is that we have to change the human being’s life, due to the concept of the sustainable development, which includes three dimensions: ecology, economy and social aspect. This paper gives the analysis of using the renewable energy, through the production of the electricity, including the sustainable development. Through research, attention was paid to analyzing the growth in the share of renewable energy in electricity production, as well as incentives to use renewable energy sources, in the area of Republic of Srpska.